Civic and citizen education: challenge of Cuban education (Review) (Revista científica Olimpia, 2020)
One of the priorities of the Revolution and of the schools in Cuba is the integral formation of the new generations. Civic education plays an important role in achieving adequate standards of conduct and coexistence. This article starts from a theoretical study related to civility in primary school children, the role of sport, using chess practice as a means. The authors consider it a pedagogical challenge to achieve comprehensiveness in children, given the current conditions facing Cuban society. Theoretical methods were used to search, review and analyze the information, which allows supporting conclusions about the importance and meaning of chess as a pedagogical tool.
Keywords: civic education; school; sport and chess